Job-Search Periods for Welfare Applicants: Evidence from a Randomized Experiment - Jonneke Bolhaar; Nadine Ketel; Bas van der Klaauw (Institute for the Study of Labor (IZA), 2016)
This paper studies mandatory job-search periods for welfare applicants. During this period the benefits application is put on hold and the applicant is obliged to make job applications. We combine a randomized experiment with detailed administrative data to investigate the effects of imposing a job-search period. We find strong and persistent effects on the probability to collect welfare benefits. The reduced benefits are fully compensated by increased earnings from work. Furthermore, we do not find evidence of adverse consequences for the most vulnerable applicants. Our results therefore suggest that a job-search period is an effective instrument for targeting welfare-benefits applicants.
Keywords: C21; C93; I38; J64; J08; 330; job search; welfare-to-work; active labor-market policies; randomized experiment